PENDIDIKAN MUSLIMAH DI ERA MILLENIAL - Susilawati Susilawati (Prosiding Seminar Nasional Indonesia, 2023)
The ease with which people can get information from the outside world without massive filtering of information by the government has resulted in external impacts that influence people's behavior, especially the millennial generation. How big or small the influence can be depends on how much of the information is interpreted as correct or accepted by the public. Especially today's millennial people who really feel the influence of globalization. An example of this is promiscuity which is misinterpreted as drinking alcohol, smoking, drug use and free sex in adolescence. For this reason, so that today's millennial generation is not negatively affected and can compete in the era of globalization, it is necessary to have preventative power and systematically and measurably planned patterns from the government through education. In accordance with Law no. 20 article 3 of 2003 concerning the National Education System states that national education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation, aiming to develop the potential of students to become human beings who believe and are devoted to God Almighty, have good morals. noble, healthy, knowledgeable, capable, creative, independent and a democratic and responsible citizen. Especially character education as a force to prevent the negative influence of globalization which is increasingly entering the living environment of Indonesian society.